The relationship between flooding parameters and grazing herbivores in the south-western Okavango Delta - Burger, Kyle (My University, 2020)
Wetlands are ecologically diverse habitats that hold significant local and global value for both people and wildlife. They provide clean water, sequester carbon, provide dry season resources for wildlife and act as important refuges for migratory birds. However, their ecological functioning relies on them remaining intact, and this is severely threatened by anthropogenic water offtake and climate change. Understanding the consequences of such changes are therefore important for successful wetland conservation and the services they provide. The Okavango Delta is a pristine, dynamic wetland system in north-western Botswana. It supports a vast array of wildlife in the middle of the Kalahari Desert, which sustains a highly profitable tourism industry. However, aerial surveys of wildlife abundance have revealed a worrying decline in certain species of herbivores, particularly those in the grazing guild. This coincides with increasing flood levels in the Okavango Delta over the same period. As the unimodal flood pulse influences the quantity and quality of grazing produced as a result of the receding flood at the end of the dry season, I set out to determine how different flood regimes may affect the grazing guild in the Okavango Delta, and whether flood patterns may explain the decline in certain species of grazers. I used a combination of vegetation transects, aerial survey data, satellite imagery and GPS collar data to determine how flooding patterns alter grazing availability, affect the structure of the grazing guild and affect resource selection at different scales. I found that during years of high flood, there is a decrease in the proportion of floodplains which consist of palatable grazing. Within the grazing guild, there was clearer separation in resource use of these floodplains during years of low flood, but in years of high flood, generalist grazers such as zebra and buffalo, converged resource use on areas favoured by specialist grazers, namely red lechwe, wildebeest and tsessebe. When examining resource use more closely in high flood years, I discovered that both generalist and specialist grazers showed increasing selection for floodplain habitat and increasing dependence on flood waters, at the home range scale and in their selection of foraging areas, in the early and late flood season, when grazing resources are otherwise scarce. Based on resource preferences during low flood years, when palatable grazing is more abundant, specialist grazers such as lechwe appeared to be slightly displaced from their favoured foraging areas. This suggests that specialist grazers may face increasing competition for grazing from generalist grazers during years of high flood, which may result in population decline of selective grazing species. Lessons learnt from this investigation may assist in the management of wetlands elsewhere whose flooding patterns alter the availability of resources at both short- and long-term timescales to ensure the maintenance of species diversity and protect endangered species
A thesis submitted to the School of Animal, Plant and Environmental Sciences, Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa in fulfillment of the requirements for the degree of Doctor of Philosophy